Estimates of Effective Population Size in Commercial and Hatchery Strains of Coho Salmon (Oncorhynchus kisutch (Walbaum, 1792)) - Martínez, Víctor; Dettleff, Phillip; Galarce, Nicolás; Bravo, Cristian; Dorner, Jessica; Iwamoto, Robert N.; Naish, Kerry (MDPI, 2022)
Understanding the genetic status of aquaculture strains is essential for developing management guidelines aimed at sustaining the rates of genetic gain for economically important traits, as well as securing populations that will be robust to climate change. Coho salmon was the first salmonid introduced to Chile for commercial purposes and now comprises an essential component of the country’s aquaculture industry. Several events, such as admixture, genetic bottlenecks, and rapid domestication, appear to be determinants in shaping the genome of commercial strains representing this species. To determine the impact of such events on the genetic diversity of these strains, we sought to estimate the effective population size (Ne) of several of these strains using genome-wide approaches. We compared these estimates to commercial strains from North America and Japan, as well as a hatchery strain used for supportive breeding of wild populations. The estimates of Ne were based on a method robust to assumptions about changes in population history, and ranged from low (Ne = 34) to relatively high (Ne = 80) in the Chilean strains. These estimates were higher than those obtained from the commercial North American strain but lower than those observed in the hatchery population and the Japanese strain (with Ne over 150). Our results suggest that some populations require measures to control the rates of inbreeding, possibly by using genomic information and incorporating new genetic material to ensure the long-term sustainability of these populations.
Keywords: Effective population size; Genetic variation; Coho salmon